SOHIBQIRON DAVRIDA O‘ZBEK MUSIQA SAN’ATINING RIVOJ TOPISHI VA UNING E’ZOZLI SOZANDASI - Burxonova, G.U. (SCIENCE and SOCIETY, 2023)
The article describes the activities of Amir Temur, in particular, his personality, which cannot be imagined without art, he tried during military campaigns to gather outstanding artists, architects, poets, musicologists, artists for Samarkand, and created opportunities for their creativity.
Keywords: activity of Amir Temur; Uzbek music; honored musician; science; literature and art